Spectral Feature Selection for Data Mining - Zheng Alan Zhao; Huan Liu (Chapman and Hall/CRC, 2012)
Spectral Feature Selection for Data Mining introduces a novel feature selection technique that establishes a general platform for studying existing feature selection algorithms and developing new algorithms for emerging problems in real-world applications. This technique represents a unified framework for supervised, unsupervised, and semisupervise